Penerapan Studio Photo Box Untuk Meningkatkan Kualitas Foto Produk dalam Pemasaran Digital UMKM Kelurahan Semolowaru - Sulthan Auliya’ Zhafran Fadhilah; Ika Sari Tondang (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In the evolving era of digital marketing, the quality of product photos plays a vital role in attracting customers and boosting sales. This study aims to explore the influence of using a studio photo box as part of the digital marketing strategy for SMEs in Semolowaru Village. A studio photo box is a simple tool made from easily accessible materials and is affordable, enabling SMEs to produce high-quality product photos. The findings of this study demonstrate that the utilization of a studio photo box can enhance the product's appeal on digital marketing platforms, attract potential customers, and differentiate the product from competitors. By using a studio photo box, SMEs in Semolowaru Village can generate attractive and professional product photos, which can contribute to building a strong brand image and increasing conversion rates. The awareness among SMEs in Semolowaru Village regarding the importance of quality product photos in digital marketing has facilitated the adoption of studio photo boxes. With the right steps, such as selecting a suitable studio, ensuring proper lighting, careful product arrangement, accurate editing, and leveraging photos in online promotions, SMEs can fully harness the potential of studio photo boxes to achieve success in digital product marketing. Studio photo box, digital marketing, product photo quality, SMEs, Semolowaru Village